PENDIDIKAN ISLAM INFORMAL DAN PERAN SUMBER DAYA MANUSIA DALAM PERKEMBANGAN MASYARAKAT: STUDI EVALUASI TEORETIS - Ahmad Tarmizi Hasibuan; Ely Rahmawati (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat Institut Agama Islam Syarifuddin Lumajang, 2022)
This study describes the study of Islamic education in an informal setting, correspondence with human resource development and the role of its development to create a healthy and balanced environment in society with moral and spiritual values. Islamic education does not only focus on formal education, but non-formal and informal education also needs to be the center of attention. Informal Islamic education contributes to the world of education in Islam, but there needs to be an evaluation in the system and its implementation, so that it can play a role in developing human resources in society. This type of research uses a qualitative approach with the Library Research method. then the data is poured by describing the results of the analysis. The results in this study contain two studies, namely, first discussing education and its functions in general and then education from an Islamic perspective. Second, it discusses the character of informal Islamic education, the role players in the field of informal Islamic education, their status as teachers, the role of teachers, teacher competencies, and teacher-student relationships in the light of Islamic culture and heritage.Keywords: Islamic Education, Human Resources.